Pengembangan Model Keilmuan PTAI Riset Berbasis Pesantren - Muhamad Husni (Proceedings of Annual Conference for Muslim Scholars, 2017)
This research about scholarship by "PTAI based pesantren" which more and more number. The main idea is "pengakuran" and "collaboration building" between traditions of pesantren and traditions of PTAI with research as the heart or academic base. With the design of a philosophy of Islamic science with the paradigm of integration-interconnection, "PTAI-based research of pesantren" on the one hand is required to reconstruct fundamentally the scientific buildings, academic system and institutional management. However, on the other hand, it is a strategic step that can not be negotiable if it wants to revitalize the functional role of PTAI-based research pesantren ", including vision, graduate profile, academic system, and so on. Of course, everything must be formulated in more detail in an academic text that actively involves stakeholders of related institutions and pesantren in an integrative-interconnective manner as the center of transforming science and the socio-cultural transformation agent for the life of society today and in the future.Kata Kunci: Development of Scientific Research, PTAI Research, and Pesantren.